PENGARUH PEMBERIAN JUS BUAH BIT TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA REMAJA PUTRI DI PANTI ASUHAN X (LPPM Universitas Sari Mulia, 2024)
Background: Iron deficiency anemia is still a major health problem in adolescent girls, especially those living in orphanages, due to inadequate nutritional intake, limited food variety, and increased iron requirements during growth and menstruation. One non-pharmacological effort that has the potential to increase hemoglobin levels is the administration of beet juice (Beta vulgaris), which is known to contain iron, folate, vitamin C, and antioxidants which play a role in the process of erythropoiesis and iron absorption. Objective: This study aims to determine the effect of giving beetroot juice on increasing hemoglobin levels in adolescent girls at Orphanage X Method: The research used a pre-experimental design with a one group pretest-posttest approach. The sample for this study was 16 teenage girls who had menstruated and had mild or moderate anemia. The intervention consisted of giving 250ml of beetroot juice once a day, for 15 days. Hemoglobin levels were measured before and after the intervention using a standard hemoglobin measuring device. Results: The results of the study showed that there was an increase in the average hemoglobin level in adolescent girls after being given beetroot juice compared to before the intervention, which means that there was an effect of giving beetroot juice on increasing hemoglobin levels in adolescent girls at Orphanage X. Keywords: Beetroot Juice, Hemoglobin, Adolescent Girls